Semiotic Analysis of Visual Illustration In The Animation “Legend of Garuda Wisnu Kencana” - Putra, Gede Lingga Ananta Kusuma; Yasa, Gede Pasek Putra Adnyana; Pramayasa, I Made Hendra Mahajaya (Jurnal Scientia, 2024)
The animation "Legend of Garuda Wisnu Kencana" is a visual work that combines art and culture to convey profound messages through dynamic graphic representations. This research aims to explore the use of visual elements in the animation, focusing on semiotic aspects involving symbols, colors, and settings. The animation serves not only as entertainment, but also as a medium for education and cultural preservation, by depicting the mythological story of Garuda, a mythical bird in Balinese culture. This research method uses a semiotic approach to analyze how visual elements, including colors, symbols, and settings, play a role in conveying cultural and mythological messages. The results of the analysis show that the characters in the animation, such as Garuda, Winata, Kadru, and the nine dragons, play an important role in building the narrative and conveying moral values such as persistence and loyalty. The use of white and gold colors and symbols such as Garuda and dragons reinforce these messages, while the Balinese cultural setting and Kahyangan Dewa provide an authentic and immersive context. The main message of the animation is the importance of striving to achieve goals and not giving up on obstacles, inspiring viewers to face challenges with determination and compassion. This research underscores how animation can serve as a bridge between art, culture and education, and provides insight into the way visual elements contribute to meaning and narrative experience in animated media.